PENGARUH SUPERVISI MANAJERIAL PENGAWAS DAN MOTIVASI KERJA TERHADAP KINERJA KEPALA SEKOLAH DI SMP SE- KABUPATEN KAMPAR - ERINTA ERINTA; MAKHDALENA MAKHDALENA; MURNI BAHERAM (Universitas Riau, 2017)
The aim of this research was to find out the effect of the manajerial supervisionsupervisor performance and work motivatio either simultaneously or partiall on headmasterperformance at state Junior High Schols (SMP) in Kampar district. The population of theresearch was headmaster of State Junior High School (SMP) Kampar-District totalling 120headmaster, with sample of 93 persons using the formula of Taro Yamane.. Form data in thisstudy are primary and sekunder. Documentation for headmaster performance and questionnairefor manajerial supervision supervisor and work motivation.Data using likert scale. Metods ofdata analysis in this study multiple regression SPSS. Research result showed that manajerialsupervision supervisor and with work motivation in positive and significant effect to theheadmaster performance either simultanaeously or partially.